Untargeted Metabolomics Analysis of Liquid Endosperm of Cocos nucifera L. at Three Stages of Maturation Evidenced Differences in Metabolic Regulation - Rufino Gómez-Tah; Ignacio Islas-Flores; Jean Wildort Félix; María Inés Granados-Alegría; Miguel Tzec-Simá; José Antonio Guerrero-Analco; Juan Luis Monribot-Villanueva; Blondy Canto-Canché (Horticulturae, 2023)
Cocos nucifera L. is one of the most cultivated palm trees in the world since it is used to obtain both raw materials and food. From a human point of view, the coconut fruit is a very valuable product, producing an aromatic and tasty liquid endosperm (coconut water) containing high levels of sugars, amino acids and other molecules of nutritional and nutraceutical value. Most of the chemical composition studies conducted on coconut to date have focused on the determination of fatty acid content in coconut oil and the extension of the shelf life of coconut water. Despite the economic importance of this species, the maturation of the coconut fruit is a complex biological process scarcely studied from the metabolic approach and biochemical changes occurring during fruit maturation are not well-known. The objective of this study is to investigate and elucidate the metabolic changes that occur during the maturation process of coconut (Cocos nucifera L.) fruits, specifically focusing on the liquid endosperm of the Yucatan green dwarf variety. In this study, the liquid endosperm of coconut fruits at the immature, intermediate and mature stages have been analyzed through an untargeted metabolomics approach by ultra performance liquid chromatography coupled to high resolution mass spectrometry (UPLC-HRMS). A total of 591 spectrometric features were detected and the corresponding identified compounds were classified into 24 chemical classes. The principal component analysis (PCA) showed segregation among the samples, according to their stage of maturation. Most of the metabolites detected were related to the metabolism of flavonoids, carbohydrates and organooxygen compounds. Pathway analysis showed that sphingolipid, starch and sucrose metabolisms were among the most over-accumulated during ripening, followed by the metabolism of glyoxylates and dicarboxylates and the metabolism of amino acids such as alanine, aspartate and glutamate, and others. This is the first study that focuses on elucidating the metabolic profiles of the liquid endosperm of coconut Yucatan green dwarf variety during three stages of maturation with an untargeted metabolomics approach through UPLC-MS.